2022
DOI: 10.1186/s12877-022-03359-y
|View full text |Cite
|
Sign up to set email alerts
|

A study on the impact of Internet use on depression among Chinese older people under the perspective of social participation

Abstract: Purpose This study aimed to evaluate the role of social participation in the relationship between internet use and depressive symptoms among Chinese older adults and investigate how the internet use interact with social participation to reduce the risk of depressive symptoms. Methods Based on the survey from the China Health and Retirement Longitudinal Study (CHARLS) in 2018, we identified 4645 subjects and used the Ordinary Least Square method (OL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Our findings are consistent with previous studies from both China and other countries. Results from Yang and his colleagues ( 29 ) based on the CHALRS indicate that older adults using the Internet had 1.8 points lower scores of depression symptoms than non-users. Cotten et al ( 7 ) estimated a one-third reduction in the depression probability among older cyber users in the United State.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with previous studies from both China and other countries. Results from Yang and his colleagues ( 29 ) based on the CHALRS indicate that older adults using the Internet had 1.8 points lower scores of depression symptoms than non-users. Cotten et al ( 7 ) estimated a one-third reduction in the depression probability among older cyber users in the United State.…”
Section: Discussionmentioning
confidence: 99%
“…We control for a range of covariates including individual and household characteristics that may be correlated with Internet use and older people’s mental health ( 9 ). In light of previous studies, we selected gender (male = 1; female = 0), age, ethnicity (Han = 1; Minority = 0), educational attainment (illiteracy = 1; primary school = 2; middle school = 3; high school and above = 4), religiosity (yes = 1; no = 0), residence status (urban areas = 1; rural areas = 0), marital status (married = 1; others = 0), and coresidence with children (yes = 1; no = 0) ( 29 , 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Depressed mood can lead to cognitive decline, an increased prevalence of chronic diseases, and even potentially life‐threatening conditions in older adults (Cheng, Thorpe, Kabir, & Lim, 2021; Sivertsen, Bjørkløf, Engedal, Selbæk, & Helvik, 2015). However, depressive symptoms are often overlooked at the time of screening because they can amplify functional impairments caused by physical illness in older adults (Bone et al., 2022; Chiao, Weng, & Botticello, 2011; Grayson & Thomas, 2013; Mirkena, Reta, Haile, Nassir, & Sisay, 2018) and are easily assumed to be the result of natural aging (Yang et al., 2022; Yang, Cheng, Ma, & Jia, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Levels of social engagement and depression vary widely across regions. While cross-sectional studies of mainland Chinese older adults Yang, Zhang, et al, 2022;Zhang, Su, Chen, Tan, & Chen, 2022) have also provided valuable information, it was impossible to establish a genuine causal relationship between social engagement and depression (Guo, Bai, & Feng, 2018). Fortunately, Li et al (2020) examined the negative effect of social engagement on depression using a mixed panel logistic model based on longitudinal data; however, the study did not examine the effect of social activity engagement on depression trajectories.…”
mentioning
confidence: 99%
“…While the pandemic may have had adverse effects on older adults without the Internet, studies with prepandemic data have shown that older adults who use the Internet may have better mental and cognitive health and social networking[26,27].An interesting study that discusses "When Going Digital Becomes a Necessity" indicated two crucial points: digitalization is insu cient in reaching older adults, and combining online and o ine strategies is invaluable in addressing the challenges older adults face[28].…”
mentioning
confidence: 99%